Effect of pre-combustion characteristics in pulse detonation engine using shchelkin spiral - C. T. Dheeraj Kumar Singh; Repaka Ramesh; Gurunadh Velidi (Carbon: Science and Technology, 2016)
Pulse detonation engines are the modern propulsive device which provides high thrust. They are unsteady propulsive devices which has multi cycle operations in it. In this multi cycle process for every cycle fuel and air are initiated and a shock wave is generated in combustion chamber in form of deflagration. Combustion chamber is maintained with high pressure and high temperature which leads to combustion of reactants. This deflagration transmits to detonation with high velocity and increasing Mach number. Deflagration propagates forward by taking all unburned species and products formed after combustion. Propagation of Deflagration – Detonation Transition (DDT) shock wave studies is a pioneering research concept. In the present study, simulation of PDE with Shchelkin spiral geometry is considered with two mass flow inlets has been used in which one is for fuel inlet and other for oxidizer. Geometry and meshing has been done in Gambit. Fuel used is gaseous fuel hydrogen and oxidizer is air mixture of O2, N2 work has been performed for different mass flow rates of fuel and oxidizer. Energy equation, Species transport equation to be solved in Fluent. Comparison results of DDT in parameters of mach number, velocity, pressure and temperatures depending on different time steps have been observed